Understanding the role of Nanomorphology on Resistance Evolution in the Hybrid Form-Fuse Process for Conformal Electronics. (October 2020) - Devaraj, Harish; Hwang, Hyun-Jun; Malhotra, Rajiv
Abstract: Manufacturing conformal electrically conductive circuits on rigid freeform surfaces currently require compromises between process scalability, cost, and thermal tolerance and geometric complexity of the object material. The Form-Fuse process operates by printing silver nanoparticle interconnects on planar polymer sheets followed by sequential vacuum forming and Flash Light Sintering (FLS) and can overcome the above issues. We investigate the role of nanoparticle morphology on this process by using nanowires (NW) in combination with nanoflakes (NF) and nanospheres (NS) as the printed nanoparticles. The characterization of FLS temperature, electrical resistance, morphology, and optical absorption along with electromagnetic and molecular dynamics modeling yields the following insights. The forming-induced resistivity rise is greater for higher NS and NF content due to localized embedding of NWs into the polymer. This embedding also reduces blowoff defects during FLS to create an expanded defect-free FLS window. The resistance reduction due to FLS is also greater for the mixed NW-NF and NW-NS cases, thanks to the change in localized optical absorption and interparticle fusion kinetics upon the introduction of NFs and NSs into a NW ensemble. The change in fusion kinetics is driven by enhanced dislocation growth between nanoparticles, despite surface and grain boundary diffusion trends contrary to the neck growth trends. We show that Form-Fuse can achieve similar or lesser electrical resistivity than state-of-the-art conformal 3D printing while enabling greater scalability and structural material capability and retaining the capability to handle complex shapes. We discuss the impact of our findings on the nanoparticle material cost and capabilities of Form-Fuse compared to other conformal electronics manufacturing processes.